Critical Functions of Region 1-67 and Helix XIII in Retaining the Active Structure of NhaD Antiporter in Halomonas sp. Y2 - Yang, Zhou; Meng, Yiwei; Zhao, Qi; Cheng, Bin; Xu, Ping; Yang, Chunyu (Frontiers in Microbiology, 2018)
NhaD-type antiporters are mainly distributed in various Proteobacteria, especially in marine microorganisms and human pathogens. This distribution as well as the pathogenic properties of these strains suggest that these antiporters contribute to the regulation of high osmoregulation and are potential drug targets. Two NhaD homologues, NhaD1 and NhaD2, from the halotolerant and alkaliphilic Halomonas sp. Y2 exhibits similar, high in vitro activity, but remarkably different in vivo functions. To search for critical domains or residues involved in these differences of physiological functions, various chimeras composed of NhaD1 and NhaD2 segments were generated. Two regions at residues 1–67 and 464–492 were found to be responsible for the robust in vivo function of NhaD2, and region 464–492 is also crucial to the pH response of the antiporter. In particular, the completely abolished activity of KNabc/N463r, highly recovered activity while very weakly recovered ion resistance of the KNabc/N463r-C7 chimera, suggested that transmembrane helix (TM) XIII is crucial for the robust ion resistance of NhaD2. Using site-directed mutagenesis, seven hydrophobic residues in TM XIII were identified as key residues for the ion translocation of NhaD2. Compared with the fluorescence resonance energy transfer (FRET) profile in the wild-type NhaD2, the reduced FRET efficiency of N463r chimeras provided solid evidence for conformational changes in the N463r fusion protein and consequently verified the structural functions of TM XIII in the pH activation and physiological functions of NhaD2.